The dynamics of risk and protective factors that shape resilience in low socioeconomic students - Taqyah, Cucu; Simanjuntak, Janice Grace Lusiani Larasati; Wedyaswari, Miryam; Dalimunthe, Karolina Lamtiur; Setyowibowo, Hari (Universitas Ahmad Dahlan, 2024)
Bidikmisi students typically originate from low socioeconomic backgrounds and encounter a variety of risk factors that impede their ability to meet the requirements of the Bidikmisi scholarship, particularly in financial terms. This study utilized a qualitative collective case study methodology to investigate the pathways leading to educational resilience by examining the interplay of protective and risk factors, which are hypothesized to differ between “resilient (n=15) and “non-resilient” (n=10) students, as determined by their Grade Point Average (GPA) and engagement in non-academic activities. Purposive sampling was employed to select Bidikmisi students based on specific criteria. Data were gathered through in-depth interviews with third-year Bidikmisi students and were analyzed using the Social Ecological and Doughnut Resilience frameworks. The findings revealed that, in addition to financial constraints, students faced several other risk factors, including inadequate learning facilities, social barriers, social pressure, familial issues, motivation deficits, personal traits, learning difficulties, and physical and psychological health challenges. Conversely, protective factors were identified within parental support, skill development, family and identity, education, peer relationships, community engagement, and financial resources.